Analisis Kebijakan Aplikasi Identitas Kependudukan Digital (IKD) Sebagai Persyaratan Pembuatan E-KTP : Studi Kasus di Kecamatan Singosari Kabupaten Malang - Iqbal Rulliansyah; Cicilia Evie P. Dewantara; Jovan Prakoso (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
Public service is an essential element that reflects the quality of governance in Indonesia, particularly in population administration, which includes the issuance of important documents such as ID cards (KTP), family cards (KK), birth certificates, and death certificates. Along with technological advancements, Indonesia launched the Digital Population Identity (IKD) application to improve efficiency and reduce reliance on physical documents. This study aims to evaluate the positive public’s response of the IKD application in Singosari District, Malang Regency, as well as to identify the challenges and factors influencing the implementation of this policy. The research method used is descriptive qualitative research with approaches such as interviews, observations, and documentation. The findings show that although the IKD application facilitates the administrative process, there are still challenges such as a lack of public’s response, limited mobile device availability, and technical issues with the application. Socialization through social media and the improvement of operator capacity are key supporting factors for the success of the implementation. This study contributes theoretically to the development of E-Governance concepts and practically highlights the importance of digital education for the public. It is suggested that enhanced socialization for groups less familiar with technology, improved supporting infrastructure, and training for service operators are necessary to ensure the success of the IKD application in population administration services in Singosari District.